Inhibition of nicotinic acetylcholine receptors by oligoarginine peptides and polyamine-related compounds - Ojomoko, Lucy O.; Kryukova, Elena V.; Egorova, Natalya S.; Salikhov, Arthur I.; Epifanova, Lyubov A.; Denisova, Daria A.; Khomutov, Alex R.; Sukhov, Dmitry A.; Vassilevski, Alexander A.; Khomutov, Maxim A.; Tsetlin, Victor I.; Shelukhina, Irina V. (Frontiers in Pharmacology, 2023)
Oligoarginine peptides, known mostly for their cell-penetrating properties, are also inhibitors of the nicotinic acetylcholine receptors (nAChRs). Since octa-arginine (R8) inhibits α9α10 nAChR and suppresses neuropathic pain, we checked if other polycationic compounds containing amino and/or guanidino groups could be effective and tested the activity of the disulfide-fixed “cyclo”R8, a series of biogenic polyamines (putrescine, spermidine, and spermine), C-methylated spermine analogs, agmatine and its analogs, as well as acylpolyamine argiotoxin-636 from spider venom. Their inhibitory potency on muscle-type, α7 and α9α10 nAChRs was determined using radioligand analysis, electrophysiology, and calcium imaging. “Cyclo”R8 showed similar activity to that of R8 against α9α10 nAChR (IC50 ≈ 60 nM). Biogenic polyamines as well as agmatine and its analogs displayed low activity on muscle-type Torpedo californica, as well as α7 and α9α10 nAChRs, which increased with chain length, the most active being spermine and its C-methylated derivatives having IC50 of about 30 μM against muscle-type T. californica nAChR. Argiotoxin-636, which contains a polyamine backbone and terminal guanidino group, also weakly inhibited T. californica nAChR (IC50 ≈ 15 μM), but it revealed high potency against rat α9α10 nAChR (IC50 ≈ 200 nM). We conclude that oligoarginines and similar polycationic compounds effectively inhibiting α9α10 nAChR may serve as a basis for the development of analgesics to reduce neuropathic pain.